Суммаро ҳисоб кунед:
\(\frac{1}{\cos{x}\cdot \cos{2x}}+\frac{1}{\cos{2x}\cdot \cos{3x}}+...+\frac{1}{\cos{9x}\cdot \cos{10x}}\)
\(S=\frac{1}{\cos{x}\cdot \cos{2x}}+\frac{1}{\cos{2x}\cdot \cos{3x}}+...+\frac{1}{\cos{9x}\cdot \cos{10x}}=\)
\(=\frac{1}{\sin{x}}\cdot(\frac{\sin{x}}{\cos{x}\cdot \cos{2x}}+\frac{\sin{x}}{\cos{2x}\cdot \cos{3x}}+...+\)
\(+\frac{\sin{x}}{\cos{9x}\cdot \cos{10x}})=\)
\(=\frac{1}{\sin{x}}\cdot(\frac{\sin{(2x-x)}}{\cos{x}\cdot \cos{2x}}+\frac{\sin{(3x-2x)}}{\cos{2x}\cdot \cos{3x}}+...+\)
\(+\frac{\sin{(10x-9x)}}{\cos{9x}\cdot \cos{10x}})\)
\(\operatorname{tg}{\alpha}-\operatorname{tg}{\beta}=\frac{\sin{(\alpha-\beta)}}{\cos{\alpha}\cdot\cos{\beta}}\)
\(S=\frac{1}{\sin{x}}\cdot(\operatorname{tg}{2x}-\operatorname{tg}{x}+\operatorname{tg}{3x}-\operatorname{tg}{2x}+...+\operatorname{tg}{10x}-\operatorname{tg}{9x})=\)
\(=\frac{1}{\sin{x}}\cdot(\operatorname{tg}{10x}-\operatorname{tg}{x})=\frac{\sin{9x}}{\sin{x}\cdot\cos{x}\cdot\cos{10x}}\)
\(2\sin{\alpha}\cdot\cos{\alpha}=\sin{2\alpha}\)
\(S=\frac{2\cdot\sin{9x}}{2\cdot\sin{x}\cdot\cos{x}\cdot\cos{10x}}=\)
\(=\frac{2\cdot\sin{9x}}{\sin{2x}\cdot\cos{10x}}\)
\(S=\frac{2\cdot\sin{9x}}{\sin{2x}\cdot\cos{10x}}\)
Ҷавоб:\(\frac{2\cdot\sin{9x}}{\sin{2x}\cdot\cos{10x}}\).